Gambaran Praktik Pencegahan COVID-19 Pada Mahasiswa Di Kota Semarang (Studi Pada Tiga Perguruan Tinggi Di Kota Semarang) - Aqmarina, Natasha; Martini, Martini; Yuliawati, Sri; Wurjanto, Moh Arie (Jurnal Ilmiah Mahasiswa, 2021)
COVID-19 is a highly contagious disease. A global pandemic or epidemic indicates a COVID-19 infection that is so fast that almost no country or region in the world is absent from this dangerous virus. COVID-19 prevention practices need to be carried out to prevent the spread of the virus from becoming more widespread, especially for students as the nation's next generation who are expected to provide a good example for the surrounding environment. This study aims to describe the description of COVID-19 prevention practices in students at three universities in the city of Semarang. This research is a descriptive study using a cross sectional approach with a population of active undergraduate students from three universities in the city of Semarang. The sample size in this study were 390 respondents. The sampling technique used is quota sampling. The research instrument used in this study was a questionnaire distributed online via social media. The results showed that the proportion of students with good COVID-19 prevention practices were female students (66.6%), students with health field of study (78.4%), and students with a good level of knowledge (69.5%). Respondents' prevention practices are good, but there are still many respondents who don’t understand about the  importance  of  COVID-19 prevention practices.  Therefore,  it  is  necessary  to  increase  the  respondent's knowledge regarding the COVID-19 prevention practices.